Investigation of GPS positioning accuracy during the seasonal variation - Dogan, U.; Uludag, M.; Demir, D. O. (ELSEVIER SCI LTD, 2014)
The aim of this study is to investigate the accuracy of GPS (Global Positioning System) positioning determined by GPS measurements carried out during the seasonal variations. The observations have been analyzed to determine how the accuracy of derived relative positions of GPS stations depends on the baseline length, the duration of observing session and the seasonal variations. For this purpose, we selected three days of each month in 2009 from the GPS observations made in the Marmara Continuous GPS Network (MAGNET). The GPS observations were processed in the ITRF 2005 reference frame using the Bernese 5.0 GPS software. The baseline length varies between 6 km and 237 km, session duration varies between 4 h and 24 h. Seasonal variation effects on the accuracy of coordinate components were analyzed. Our results showed that seasonal variation is a significant factor for determining the accuracy of GPS measurements. Also, increasing the observation period hardly improves the horizontal positioning accuracy while improving the vertical positioning accuracy. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: GPS; Accuracy analysis; Seasonal effect; Session; Duration; Baseline length; CRUSTAL DEFORMATION; RELATIVE POSITIONS; MARMARA REGION; SYSTEM; PRECISION; DISTANCE; TURKEY; IZMIT; Engineering; Instruments & Instrumentation